Magnesium iodide-catalyzed synthesis of 2-substituted quinazolines using molecular oxygen and visible light. Issue 62 (13th June 2016) - Yamaguchi, T.; Sakairi, K.; Yamaguchi, E.; Tada, N.; Itoh, A.
Abstract : We disclose a novel and efficient synthesis of 2-substituted quinazolines by aerobic photooxidative reaction catalyzed by magnesium iodide. Abstract : A novel and efficient approach for the synthesis of quinazolines by aerobic photooxidation with an iodine reagent at room temperature is reported. This method uses harmless visible light from compact fluorescent lamps and molecular oxygen as the sole oxidant without the need for a transition-metal catalyst or harsh reaction conditions.